MANAJAMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN KEMAMPUAN SOFTSKILLS DAN HARDSKILLS SISWA DI SMK MUSIK - Muhammad Farhan Ramadhan; Riyan Arthur (Universitas Muria Kudus, 2022)
The purpose of this study was to describe the character education management process in developing the soft skills and hard skills of students at the Cikini College Music Vocational School. The research method used in this research is to use a descriptive qualitative approach. The study was conducted from March to May 2022. The data collection technique used in this research is through interviews, observations, and document studies. The subjects of this study were vice principals, teachers, disciplinary committees, and students. The data analysis technique used is descriptive data analysis technique.The data validity technique uses the Milles and Huberman data triangulation method. The results of this study indicate that the character education management process in developing the soft skills and hard skills of students at the Cikini Music Vocational School begins with a program planning process that is integrated into the school's vision and mission and involves teachers, school structures, disciplinary commissions, as well as education and training staff. school committees and organizing processes are carried out by collaborating with human resources in schools in carrying out school programs, implementation is carried out by all teachers and students in accordance with the tasks that have been distributed, and evaluation and supervision are carried out every week by involving internal and external parties. In general, the implementation of the development of students' soft skills and hard skills is integrated into learning activities, habituation, boarding, and independent training with students and productive teachers or music teachers while students are at school.